A controlled chamber study of effects of exposure to diesel exhaust particles and noise on heart rate variability and endothelial function. (12th May 2022) - Stockfelt, Leo; Xu, Yiyi; Gudmundsson, Anders; Rissler, Jenny; Isaxon, Christina; Brunskog, Jonas; Pagels, Joakim; Nilsson, Patrik T.; Berglund, Margareta; Barregard, Lars; Bohgard, Mats; Albin, Maria; et al.
Abstract: Background: Adverse cardiovascular effects are associated with both diesel exhaust and road traffic noise, but these exposures are hard to disentangle epidemiologically. We used an experimental setup to evaluate the impact of diesel exhaust particles and traffic noise, alone and combined, on intermediary outcomes related to the autonomic nervous system and increased cardiovascular risk. Methods: In a controlled chamber 18 healthy adults were exposed to four scenarios in a randomized cross-over fashion. Each exposure scenario consisted of either filtered (clean) air or diesel engine exhaust (particle mass concentrations around 300 µg/m 3 ), and either low (46 dB(A)) or high (75 dB(A)) levels of traffic noise for 3 h at rest. ECG was recorded for 10-min periods before and during each exposure type, and frequency-domain heart rate variability (HRV) computed. Endothelial dysfunction and arterial stiffness were assessed after each exposure using EndoPAT 2000. Results: Compared to control exposure, HRV in the high frequency band decreased during exposure to diesel exhaust, both alone and combined with noise, but not during noise exposure only. These differences were more pronounced in women. We observed no synergistic effects of combined exposure, and no significant differences between exposure scenarios for other HRV indices, endothelial function or arterial stiffness. Conclusion: Three-hour exposure to diesel exhaust, but not noise, was associated with decreased HRV in the high frequency band. This indicates activation of irritant receptor-mediated autonomic reflexes, a possible mechanism for the cardiovascular risks of diesel exposure. There was no effect on endothelial dysfunction or arterial stiffness after exposure.